2022
DOI: 10.3389/fpsyg.2022.923482
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Expression in Modern Literary Appreciation: An Emotion-Based Analysis

Abstract: BackgroundModern literary appreciation seems to be reading literary works phenomenally. In fact, appreciation is not a general reading, which has an important difference from general reading. It is the identification and appreciation of literary works and a complex spiritual activity for people to feel, understand, and imagine literary and artistic works. At the same time, literary appreciation is also a cognitive activity, an aesthetic activity, and a re-creation activity.MethodIn this paper, the machine lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The results of the study support earlier research that found films as a form of literature encourage students to think critically (Abbas & Salih, 2019;Lanta et al, 2019;Nushur & Astutie, 2021;Sánchez-Auñón et al, 2023). The results also demonstrate the notion that emotional conflict hinders students from blindly accepting the film's message (Harold, 2010) and establishes the audience's relationship to the film (Li, 2022). Students supported a woman's resistance, which Berglund et al (2023) conceptualized as the process of finding and strengthening her voice and beliefs.…”
Section: Discussionmentioning
confidence: 63%
“…The results of the study support earlier research that found films as a form of literature encourage students to think critically (Abbas & Salih, 2019;Lanta et al, 2019;Nushur & Astutie, 2021;Sánchez-Auñón et al, 2023). The results also demonstrate the notion that emotional conflict hinders students from blindly accepting the film's message (Harold, 2010) and establishes the audience's relationship to the film (Li, 2022). Students supported a woman's resistance, which Berglund et al (2023) conceptualized as the process of finding and strengthening her voice and beliefs.…”
Section: Discussionmentioning
confidence: 63%
“…Li [23] have presented emotion expression in modern literary appreciation: emotion-depend analysis. This article analyses the emotions that writers intended to portray in contemporary literary works by utilizing a machine learning algorithm in a unique way to categories the emotions of characters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human expressions unveil a lot of stories. Emotional expression is a connector between literature and people (Li, 2022). Literary work is a part of literature which is formed by an idea or feeling (Mutiarani, 2017).…”
Section: Introductionmentioning
confidence: 99%